Realising the density dividend? Changes in urban lifestyle and culture as compact developments emerge on Cape s public transport corridors - Mckenzie, Katharine (Department of Civil Engineering, 2017)
Local planning reform has facilitated the development of some higher density residential and mixed-use development on Cape Town's transport corridors, laying the basis for more efficient and sustainable lifestyles in areas of the city served by public transport and paratransit services. The research aims to explore the lifestyle changes that these new denser developments, viewed as a form of nascent transit-oriented development (TOD), have ushered in and their potential to contribute to the creation of inclusive urban communities. The research explores this through the development of four qualitative case studies, each in a different part of the city, with different transport and urban features. The case studies each focus on relatively new multi-storey residential developments exploring the intentions of the developers in relation to their target markets, as well as the lived experience of the residents of these developments. The key findings are that in areas with the features, services and amenities associated with transit-oriented development, residents are embracing new urban lifestyles based on walking and public transport use. Barriers to this include the failure of public transport, particularly the rail system, to adhere to existing timetables and service levels, or to expand these beyond the traditional weekday peak service. The research concludes that in well-located developments on public transport corridors with good urban management, behaviour change on the part of residents can be observed. This shift to more sustainable lifestyles will be bolstered by further improvements in the provision of public transport services, non-motorised transport infrastructure and paratransit services, as well as the strategic management of parking policy and practice to support TOD lifestyles.